Mediating effect of mutuality on caregiver burden in Parkinson's disease partners. (1st September 2020) - Karlstedt, Michaela; Fereshtehnejad, Seyed-Mohammad; Aarsland, Dag; Lökk, Johan
Abstract: Objectives: Parkinson's disease (PD) is a complex neurodegenerative disorder with a broad list of motor and non-motor symptoms (NMS) that has been shown to affect the relationship quality (mutuality) and caregiver burden. However, little is known if the effect of motor and NMS on caregiver burden is mediated by mutuality. Therefore, the aim of this study was to explore if perceived mutuality by patients and partners mediates the effect of motor and NMS on caregiver burden. Methods: Data were collected from 51 dyads with one PD patient, including measures of motor signs, NMS, impaired cognition, patients' and partners' perceived mutuality, caregiver burden and dependency in activities in daily life (ADL). Structural equation model with manifest variables were applied to explore if patients' and partners' mutuality score mediated the effect of motor signs, NMS, ADL or impaired cognition on caregiver burden. Result: Our results suggest that having a partner with PD who is dependent in ADL or has impaired cognition decreases partners' mutuality which leads to elevated burden. Motor symptoms or other NMS were not associated with partners' mutuality or caregiver burden. Instead, increasing severity of motor symptoms decrease patients' mutuality in turn leading to lower level of partners' mutuality. Conclusion: Our findings enhance the understanding of the complexity of living with PD for the partner and suggest that clinical assessment should include evaluation of how PD symptoms influence the quality of the relationship between partners and patients.